2015
DOI: 10.1111/exd.12751
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast‐specific upregulation of Flightless I impairs wound healing

Abstract: The cytoskeletal protein Flightless (Flii) is a negative regulator of wound healing. Upregulation of Flii is associated with impaired migration, proliferation and adhesion of both fibroblasts and keratinocytes. Importantly, Flii translocates from the cytoplasm to the nucleus in response to wounding in fibroblasts but not keratinocytes. This cell-specific nuclear translocation of Flii suggests that Flii may directly regulate gene expression in fibroblasts, providing one potential mechanism of action for Flii in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Statistical Analysis : Statistical differences were determined using the Student's t ‐test or an ANOVA. For data not following a normal distribution, the Mann–Whitney U‐test was performed . A P ‐value of less than 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Statistical Analysis : Statistical differences were determined using the Student's t ‐test or an ANOVA. For data not following a normal distribution, the Mann–Whitney U‐test was performed . A P ‐value of less than 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…A decrease in Flii expression, either endogenously in heterozygous knockout mice or via the topical application of a neutralizing antibody raised against the leucine-rich repeat domain in murine and porcine wound models, results in improved healing (Cowin et al, 2007;Jackson et al, 2012;Strudwick and Cowin, 2012). Conversely, overexpression of Flii in the mouse resulted in larger scars, with a slower, impaired wound healing response (Cowin et al, 2007;Jackson et al, 2012;Strudwick and Cowin, 2012), with fibroblast-specific upregulation of Flii giving a similar magnitude of wound healing impairment to non-tissuespecific upregulation (Turner et al, 2015). However, Flii also has a positive effect on hair follicle regeneration, with Flii overexpression resulting in significantly longer hair fibers in regenerated follicles and reduced Flii expression resulting in delayed regeneration (Waters et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study showed that Flii competes with MyD88 by binding to the TIR region of TLR4 and inhibits the formation of the TLR4/MyD88 signalling complex required for activation of cytokine secretion pathways . Flii expression in the skin is upregulated during development and in response to inflammation, tissue injury, skin cancer development and hypertrophic scarring . A recent study in an in vivo model of diabetic wound healing, showed that decreasing cutaneous Flii levels was associated with reduced inflammation and levels of TLR4 expression .…”
mentioning
confidence: 99%